2014
DOI: 10.1007/s10064-014-0676-7
|View full text |Cite
|
Sign up to set email alerts
|

Stress–strain behaviour of the sediments in the tertiary basins associated with the Alentejo–Plasencia fault in the province of Caceres (Spain)

Abstract: An analysis of the geotechnical information obtained from a large number of field tests (pressuremeter) and laboratory tests (identification, state, and mechanics) on the clay deposits in the small tertiary basins associated with the Alentejo-Plasencia fault in the province of Caceres (Spain) has made it possible to classify them and predict their response to different levels of stress and strain. This geotechnical classification process must consider an appropriate model of constitution. The present article i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…erefore, the key to solving the turfy soil problem is to establish the constitutive model that can reasonably describe its soil strength and deformation characteristics [9]. Experimental studies have shown that the stress history, stress pathways, and physical state of the soil, such as its composition structure, have a significant impact on its constitutive model [10][11][12]. Turfy soil contains a considerable degree of plant residue and organic matter, and the influence of the stress pathways on the constitutive model will be more significant because of the complexity of its composition and structure [13].…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the key to solving the turfy soil problem is to establish the constitutive model that can reasonably describe its soil strength and deformation characteristics [9]. Experimental studies have shown that the stress history, stress pathways, and physical state of the soil, such as its composition structure, have a significant impact on its constitutive model [10][11][12]. Turfy soil contains a considerable degree of plant residue and organic matter, and the influence of the stress pathways on the constitutive model will be more significant because of the complexity of its composition and structure [13].…”
Section: Introductionmentioning
confidence: 99%